First principle study of inorganic metal halide perovskites for solar cells application - Maleka, Prettier Morongoa (University of the Witwatersrand, Johannesburg, 2024)
All-inorganic halide perovskites have received significant attention as semiconductor materials due to their outstanding opto-electronic properties, which have achieved power conversion efficiency (PCE) of up to 25% in perovskite solar cells. Their exceptional characteristics include long diffusion lengths for electrons and holes, tuneable band gap, high absorption coefficients, small effective masses, high carrier mobility, and simple reproducible process. Despite these excellent properties, metal halide perovskites have drawbacks that negatively affect the PCE and stability of the perovskite solar cell devices. This study investigated all-inorganic halide perovskite, CsPbI3, by employing the first-principle density functional theory (DFT) method. Firstly, the effect of mixing halides on X-site was investigated to probe the structural stability and opto-electronic properties. The structural, electronic, optical, mechanical and thermodynamics properties of CsPbI3 – xBrx were investigated using three exchange correlation functionals, namely, LDA, GGA-PBE and SCAN meta-GGA. The findings revealed that mixed halide perovskites have an ideal direct energy band gap for suitable photovoltaic applications. For GGA-PBE and SCAN meta GGA exchange correlation functionals, the determined energy band gap ranges from 1.33 eV and 1.877 eV, whereas the LDA band gap ranges between 0.960 eV and 1.137 eV. The electronic band gaps predicted by GGA-PBE and SCAN meta GGA exchange correlation, which offer better precision compared to LDA suggest that Br-doped CsPbI3 – xBrx perovskite is suitable for photons absorption from near-infrared to visible regions of the spectrum. The modification of the band gap is an essential feature of photovoltaics, as it enables the optimization of solar cell performance. In addition, the systems CsPbI3, CsPbI2Br, CsPbIBr2, and CsPbBr3 exhibited exceptional mechanical and thermodynamic stability. Secondly, perovskites that are considered for photovoltaic applications contain toxic element lead (Pb) on the B-site, which limits application of these perovskites in photovoltaic devices. In this study, substitution of toxic Pb with a smaller percentage of selected transition metals was investigated in order to alleviate the toxicity problems. Thus, CsPbI3 doped with 12.5 % concentration of transition metal, Mn, Fe, Ni and Zn was investigated using DFT. The results showed that transition metal doped-CsPbI3 perovskites enhanced the absorption of this material, although they are all indirect band gaps semiconductors. All the materials were found to be mechanically stable. Lastly, cluster expansion which is a method that is capable of describing the concentration dependent thermodynamic properties of materials while maintaining DFT accuracy, was used to predict new (CsPbI/Br)3 structures. The cluster expansion method generated 42 new stable (CsPb)xIyBrz (where x = 1 to 3 and y and z = 1 to 8) structures and these were ranked the meta-stable structures based on their formation enthalpies. Monte Carlo calculations showed that CsPbI0.5Br0.5 composition separates into different phases at 300K, but changes to homogeneous phase at 700 K, suggesting that a different phase of CsPbI3 may exist at higher temperature. Among the 42 predicted structures, randomly selected structures around iodide rich, 50:50 and bromine rich sites were studied further by determining their electronic, optical, mechanical and thermodynamic properties using DFT. The materials possess similar properties as cubic Br doped CsPbI3 perovskites. The mechanical properties of these compounds revealed that they are ductile in nature and mechanically stable. In summary, the thesis present a novel work on introduction of impurities into CsPbI3 perovskite material as well as compositional engineering to alter its electronic and optical properties for solar cells application.
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Perovskites Solar Cells; Optoelectronic properties; Density Functional Theory; Doping; Band Structure; Dielectric Function; Power Conversion Efficiency; Monte-Carlo; Cluster Expansion; Transition Metals; Absorption Coefficient; Photovoltaic Efficiency; Elastic properties; Refractive index; Mixed-Halide Perovskite; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-7: Affordable and clean energy